ChemInform Abstract: A Highly‐Efficient Palladium‐Catalyzed Aminocarbonylation/SNAr Approach to Dibenzoxazepinones. Issue 38 (3rd September 2015) - Shen, Chaoren; Neumann, Helfried; Wu, Xiao‐Feng
Abstract Various 2‐aminophenols and 2‐bromofluorobenzenes are used as substrates for the convenient one‐pot synthesis of a wide range of dibenzoxazepinones by a palladium‐catalyzed aminocarbonylation/aromatic nucleophilic substitution sequence.